Handbook of research on advancements in robotics and mechatronics - Habib, Maki K., 1955- (Advances in computational intelligence and robotics (ACIR) book series., 2015)
"This book presents new findings, practices, technological innovations, and theoretical perspectives on the the latest advancements in the field of mechanical engineering assisting engineers and scientists, students, researchers, and practitioners looking to develop autonomous and smart products and systems for meeting today's challenges"--